2007
DOI: 10.1007/s10815-007-9144-7
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of pregnancy in IVF cycles on the fourth day of ovarian stimulation

Abstract: Purpose Prediction of IVF outcome on the first days of ovarian stimulation has focused clinical research for many years. The aim of this work is to predict the probability of pregnancy on the fourth day of ovarian stimulation for IVF cycle, using parameters usually determined in this stageestradiol, antral follicle count-together with parameters determined previously: FSH on the third day of cycle and women age. Materials and methods One hundred and ten patients with primary infertility due to a tubal factor w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The prediction of assisted reproduction treatment outcome has been the focus of clinical research for many years, with a variety of prognostic models describing the probability of an ongoing pregnancy or a live birth following treatment. To date, models have predominantly been established using patient baseline characteristics and although these models have been heterogeneous in their performance they consistently demonstrate that certain patient characteristics are associated with IVF/intracytoplasmic sperm injection (ICSI) success, including female age (Bancsi et al, 2000;Bouckaert et al, 1994;Carrera-Rotllan et al, 2007;Commenges-Ducos et al, 1998;Hughes et al, 1998;Hunault et al, 2002;Hull et al, 1996;Lee et al, 2009;Lintsen et al, 2005;Minaretzis et al, 1998;Ottosen et al, 2007;Stolwijk et al, 1996;Stolwijk et al, 2000;Templeton et al, 1996;van Weert et al, 2008;Younis et al, 2009), duration of infertility (Haan et al, 1991;Lintsen et al, 2007;Younis et al, 2009), pregnancy history (Lintsen et al, 2007;Stolwijk et al, 2000;Templeton et al, 1996;van Weert et al, 2008), diagnostic category (Bancsi et al, 2000;Lintsen et al, 2007;van Weert et al, 2008) and body mass index (BMI;Ferlitsch et al, 2004;Verberg et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prediction of assisted reproduction treatment outcome has been the focus of clinical research for many years, with a variety of prognostic models describing the probability of an ongoing pregnancy or a live birth following treatment. To date, models have predominantly been established using patient baseline characteristics and although these models have been heterogeneous in their performance they consistently demonstrate that certain patient characteristics are associated with IVF/intracytoplasmic sperm injection (ICSI) success, including female age (Bancsi et al, 2000;Bouckaert et al, 1994;Carrera-Rotllan et al, 2007;Commenges-Ducos et al, 1998;Hughes et al, 1998;Hunault et al, 2002;Hull et al, 1996;Lee et al, 2009;Lintsen et al, 2005;Minaretzis et al, 1998;Ottosen et al, 2007;Stolwijk et al, 1996;Stolwijk et al, 2000;Templeton et al, 1996;van Weert et al, 2008;Younis et al, 2009), duration of infertility (Haan et al, 1991;Lintsen et al, 2007;Younis et al, 2009), pregnancy history (Lintsen et al, 2007;Stolwijk et al, 2000;Templeton et al, 1996;van Weert et al, 2008), diagnostic category (Bancsi et al, 2000;Lintsen et al, 2007;van Weert et al, 2008) and body mass index (BMI;Ferlitsch et al, 2004;Verberg et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover it has been clearly demonstrated that in models predicting pregnancy based on intermediate results (at embryo transfer), the number of retrieved and fertilized oocytes have the highest prognostic value (Ferlitsch et al, 2004;Verberg et al, 2007). This suggests that any marker which can predict the number of retrieved oocytes prior to ovarian stimulation may be of value in initial baseline prognostic models (Bancsi et al, 2000;Carrera-Rotllan et al, 2007;Ferlitsch et al, 2004;Lee et al, 2009;Ottosen et al, 2007;Younis et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between the AFC and reproductive age is now well recognized (7,(10)(11)(12)(13)(14), and the prognostic value of the AFC in ART treatment is well established (3,8,13,(15)(16)(17)(18)(19)(20)(21). Early follicular-phase AFC also has a predictive value for ovarian response to ART that is better or at least equivalent to that of complex hormonal tests, such as the exogenous FSH ovarian reserve test and the clomiphene citrate challenge test (22).…”
mentioning
confidence: 99%
“…The AFC has also been used as a predictor of ovarian reserve (12)(13)(14)(15)(16)(17)(18)(19)(20)(21). Recent studies have shown that AMH and the AFC are equally effective in predicting poor ovarian response in an IVF program (18,19,21).…”
mentioning
confidence: 99%